Heat transfer enhancement in two-start spirally corrugated tube - Kareem, Zaid Sattar (Elsevier, 2015)
Various techniques have been tested on heat transfer enhancement to upgrade the involving equipment, mainly in thermal transport devices. These techniques unveiled significant effects when utilized in heat exchangers. One of the most essential techniques used is the passive heat transfer technique. Corrugations represent a passive technique. In addition, it provides effective heat transfer enhancement because it combined the features of extended surfaces, turbulators and artificial roughness. Therefore, A Computational Fluid Dynamics was employed for water flowing at low Reynolds number in spiral corrugated tubes. This article aimed for the determination of the thermal performance of unique smooth corrugation profile. The Performance Evaluation Criteria were calculated for corrugated tubes, and the simulation results of both Nusselt number and friction factor were compared with those of standard plain and corrugated tubes for validation purposes. Results showed the best thermal performance range of 1.8-2.3 for the tube which has the severity of 45.455 × 10-3 for Reynolds number range of 100-700. The heat transfer enhancement range was 21.684%-60.5402% with friction factor increase of 19.2-36.4%. This indicated that this creative corrugation can improve the heat transfer significantly with appreciably increasing friction factor